To What Extent Is a Transition into Employment Associated with an Exit from Poverty - Taryn Ann Galloway (Statistics Norway, Research Department, 2004)
A link between lack of employment and poverty is often made implicitly, but can be difficult to enumerate in a satisfactory manner. We would therefore like to ask the question: to what extent does acquiring employment increase a poor household's probability of exiting poverty? Register data from the entire resident population of Norway serves as the basis for this analysis, which indicates that full-time does greatly increase the probability of exiting poverty. Part-time employment also has an effect, albeit a small one. Findings with respect to transfers are compatible with certain disincentives related to employment for single mothers, although similar results cannot be found for other types of households.
Keywords: I32; J20; 330; Unemployment; Employment; Poverty